Peran Komitmen Sebagai Mediasi pada Pengaruh Kecerdasan Emosional dan Supervisi Terhadap Kinerja Pegawai - Dwi Poetri, Nadya; Sudarwati; Mariyam, Siti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to examine and analyze the role of commitment as a mediator in the influence of emotional intelligence and supervision on employee performance. This research method uses a quantitative descriptive design. The population was all employees of SMP Muhammadiyah 5 Surakarta, totaling 38 respondents and the samples used were taken from the entire population. The sampling technique uses census sampling. Data collection uses a questionnaire. The data analysis techniques used are descriptive statistical tests, measurement model tests or outer models including convergent validity, discriminant validity and reliability, structural model tests or inner models including r-square, f-square and estimated path coefficients, hypothesis tests and mediation tests The results of this research show that the variables of emotional intelligence and supervision have a positive and significant effect on employee performance variables through commitment. In this study, the resulting Adjusted R-Square was Y 0.902 or 92.0% and Z 0.864 or 86.4%.